Speed of reaction and fighting effectiveness in elite greco-roman wrestlers - Gierczuk, D.; Lyakh, V.; Sadowski, J.; Bujak, Z. (Perceptual and Motor Skills, 2017)
The purpose of the study was to determine the changes in simple reaction time and to define correlations between simple reaction time and technical and tactical actions performed by elite Greco-Roman wrestlers during a match. Twenty Greco-Roman wrestlers (M age = 19.5 years, SD = 1.8) from the Wrestling Sports Centre in Radom participated in the study. Simple reaction time (including reaction time and movement time) before a match and after the first, the second, and the third round was analyzed. The wrestlers' reaction time and movement time changed in the course of performance. Wrestlers with higher sports achievements demonstrated a smaller decrement in simple reaction time and performed more technical and tactical actions during a match. The strongest correlations were observed between both reaction time and movement time and the number of technical and tactical actions performed during the last round. Quick reaction was a significant factor in determining the match outcome, which is revealed at submaximal intensity of the effort during a match. ABSTRACT FROM AUTHOR